Emerging Therapeutic Potential of Cannabidiol (CBD) in Neurological Disorders: A Comprehensive Review - Kuldeep Singh; Bharat Bhushan; Dilip Kumar Chanchal; Satish Kumar Sharma; Ketki Rani; Manoj Kumar Yadav; Prateek Porwal; Shivendra Kumar; Ashwani Sharma; Tarun Virmani; Girish Kumar; Abdullah Al Noman (Behavioural Neurology)
Cannabidiol (CBD), derived from Cannabis sativa, has gained remarkable attention for its potential therapeutic applications. This thorough analysis explores the increasing significance of CBD in treating neurological conditions including epilepsy, multiple sclerosis, Parkinson’s disease, and Alzheimer’s disease, which present major healthcare concerns on a worldwide scale. Despite the lack of available therapies, CBD has been shown to possess a variety of pharmacological effects in preclinical and clinical studies, making it an intriguing competitor. This review brings together the most recent findings on the endocannabinoid and neurotransmitter systems, as well as anti-inflammatory pathways, that underlie CBD’s modes of action. Synthesized efficacy and safety assessments for a range of neurological illnesses are included, covering human trials, in vitro studies, and animal models. The investigation includes how CBD could protect neurons, control neuroinflammation, fend off oxidative stress, and manage neuronal excitability. This study emphasizes existing clinical studies and future possibilities in CBD research, addressing research issues such as regulatory complications and contradicting results, and advocates for further investigation of therapeutic efficacy and ideal dose methodologies. By emphasizing CBD’s potential to improve patient well-being, this investigation presents a revised viewpoint on its suitability as a therapeutic intervention for neurological illnesses.